Foreign policy thinking outside the box - Etzioni, Amitai (Routledge, Taylor & Francis Group, 2016)
This collection of essays by renowned scholar Amitai Etzioni aims to provoke reconsiderations of basic assumptions of foreign policy by students, academics and practitioners.